2010
DOI: 10.1074/jbc.m110.139477
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine Biosynthesis during Neuronal Differentiation and Its Role in Cell Fate Determination

Abstract: Neuronal differentiation is characterized by neuritogenesis and neurite outgrowth, processes that are dependent on membrane biosynthesis. Thus, the production of phosphatidylcholine (PtdCho), the major membrane phospholipid, should be stimulated during neuronal differentiation. We demonstrate that during retinoic acid (RA)-induced differentiation of Neuro-2a cells, PtdCho synthesis was promoted by an ordered and sequential activation of choline kinase ␣ (CK␣) and choline cytidylyltransferase ␣ (CCT␣). Early af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 64 publications
5
67
1
2
Order By: Relevance
“…ERK1/2 are kinases of the MAPK family involved in the regulation of many cellular processes, especially in cell proliferation and differentiation [23] . It has also been reported that RA switches on a genetic program involving ERK1/2 activation [24] . We measured ERK1/2 phosphorylation ratios at DIV5 and DIV9 in SH-SY5Y cells under control conditions, after induction of differentiation by RA and after PREP inhibition with 10 M JTP-4819 ( fig.…”
Section: Prep and The Cell Signalling System In Sh-sy5y Cellsmentioning
confidence: 99%
“…ERK1/2 are kinases of the MAPK family involved in the regulation of many cellular processes, especially in cell proliferation and differentiation [23] . It has also been reported that RA switches on a genetic program involving ERK1/2 activation [24] . We measured ERK1/2 phosphorylation ratios at DIV5 and DIV9 in SH-SY5Y cells under control conditions, after induction of differentiation by RA and after PREP inhibition with 10 M JTP-4819 ( fig.…”
Section: Prep and The Cell Signalling System In Sh-sy5y Cellsmentioning
confidence: 99%
“…5b). Differentiation coincides with increased production of phosphatidylcholine [27] due to the increased surface area that is needed to meet the physical demands of concavity that is associated with neuritic growth. We observed that neuritic processes were preferentially affected by SDM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest levels for ChoK ␣ were recorded at 28 h after serum stimulation, and the enzyme activity displayed a delayed profi le across time, likely refl ecting the time required for translation. Strikingly, ChoK has been shown to be strongly expressed in tumor cells ( 36 ), and although this enzyme is not the rate-limiting enzyme in PC synthesis, it has been proposed to function as a key regulatory enzyme ( 27,32,33 ) that seems to be tightly regulated in a circadian manner. Our results suggest that this enzyme may temporally control the biosynthesis of PC in synchronized cells.…”
Section: Time-related Mechanisms Modulate the Biosynthesis Of Pc In Cmentioning
confidence: 99%
“…However, it has been demonstrated that the availability of diacylglycerol (DAG) and regulation of ChoK also infl uence PC biosynthesis ( 27,32,33 ). In most mammals, there are two genes encoding for ChoK: Chka codes for ChoK ␣ 1/2 and Chkb codes for ChoK ␤ ( 34,35 ).…”
mentioning
confidence: 99%